Effect of boron on yield and physiological properties in rape (Brassica campestris) - MANDAL, MITALI; DAS, DILIP KUMAR (The Indian Journal of Agricultural Sciences, 2014)
The results of the present investigation show that the physiological properties as well as yield of rape (Brassica campestris L.) have been found to be affected by integrated applications of B and well rotten farmyard manure. The activity of indole acetic acid (IAA) oxidase was recorded a lowest value in the treatment T4 where recommended N: P2O5: K2O (80:40:40), boron at 0.5 kg/ha as calbor and well rotten farmyard manure at 5 tonnes/ha was applied. The IAA was highest in control treatment suggesting crops may suffer due to boron deficiency with an increase in IAA oxidase activity. The highest value of polyphenol oxidase (PPO) with no boron application exhibited boron deficiency while that of the same recorded a lowest value with the application of boron at 0.5 kg/ha along with 5 tonnes/ha well rotten farmyard manure did not show any boron deficiency. The highest and lowest polyphenol activity were recorded in the treatment T1 and T4 where no boron and boron at 0.5 kg/ha along with 5 tonnes/ha well rotten farmyard manure was applied respectively.